Uwarunkowania kulturowe procesów negocjacyjnych w krajach Azji Południowo-Wschodniej - Kałążna-Drewińska, Urszula (Cultural conditions of negotiation processes in countries of Southeast Asia, 2009)
Integration processes in countries of Southeast Asia, members of ASEAN (Association of Southeast Asia Nations), imply the necessity of reflection on the development of relations between the subjects of the market of countries associated with this organization and those remaining outside this organization. The basis for these relations in an ever increasing rate and scope have become negotiations. Cultural conditions play an important role in these negotiations, they influence to a great extent negotiation behaviour. In the search of negotiation behaviour cultural typologies demonstrate high usability. The paper describes two of them: G. Hofstede’s typology and R. Gesteland’s typology referring to Southeast Asia countries. Knowing them enables a better preparation, understanding and executing negotiations, and the use of cultural differences to reach an agreement useful for all negotiating sides
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67, s. 165-175